Preparation method of nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst

Through the preparation method of nickel-doped bismuth oxyhalide/g-C3N4 composite catalyst, the problem of low photo-quantum efficiency of g-C3N4 is solved, and higher photocatalytic performance and stability are achieved.

CN116273114BActive Publication Date: 2025-04-08NORTHWEST RES INST OF MINING & METALLURGY INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310114503.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-15
Publication Date
2025-04-08
Estimated Expiration
2043-02-15

AI Technical Summary

Technical Problem

g-C3N4 has low light quantum efficiency and low effective utilization of visible light.

Method used

The Ni-doped BiOX-g-C3N4 composite catalyst was prepared by the preparation method of nickel-doped bismuth oxyhalide/g-C3N4 composite catalyst through hydrothermal reaction and ultrasonic dispersion.

Benefits of technology

The photocatalytic performance of the composite catalyst is improved, the degradation rate reaches 87.32%-91.78%, and the material is stable and dispersible.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273114B_ABST
    Figure CN116273114B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, comprising the following steps: step one, preparing g-C3N4; step two, preparing BiOX-g-C3N4; step three, preparing the nickel-doped BiOX-g-C3N4 composite catalyst. According to the invention, Ni ions are doped with the catalyst BiOX-g-C3N4 to greatly improve the photocatalytic performance of the material, the doping of Ni ions generates more oxygen holes, suppresses the recombination of photogenerated electrons-holes, causes the light absorption edge of g-C3N4 to red-shift, reduces the energy of photogenerated electrons transitioning from the valence band to the conduction band of g-C3N4, reduces the bandgap width of the composite catalyst, and improves the photocatalytic activity of the BiOX-g-C3N4 composite photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysts, and in particular to a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst. Background Art

[0002] Semiconductor photoelectrocatalysis is an effective way to solve the current environmental pollution and energy crisis. Graphene carbon nitride (g-C3N4) is a new type of non-metallic semiconductor material with a graphene layered structure. Its bandgap is

[0003] 2.7 eV, which crosses the redox window of water, and has obvious light absorption in the visible light region. The unique semiconductor band structure and excellent thermal and chemical stability of g-C3N4 have attracted widespread attention as a highly potential photocatalyst in the field of photocatalysis such as water splitting and degradation of organic pollutants. However, like most semiconductor materials, the high photogenerated electron-hole recombination rate leads to low photoquantum efficiency of g-C3N4, which seriously restricts its practical application. At the same time, although g-C3N4 is a visible light semiconductor material, its effective utilization of visible light is not high. Studies have found that composites with other functional semiconductor materials can effectively promote the separation and transfer of photogenerated carriers, and the heterogeneous composite of two-dimensional layered materials has a larger contact interface than other dimensional composite materials, which is more conducive to the transfer of photogenerated carriers at the interface, thereby showing more ideal photocatalytic activity.

[0004] Among other functional materials, bismuth oxyhalide (BiOX) has a band gap of only 2.5-2.9 eV, has good visible light absorption and photoelectrocatalytic performance, and has a similar layered structure to g-C3N4, and its intrinsic energy band position constitutes a typical type II heterogeneous energy band structure. Therefore, the heterogeneous composite of g-C3N4 and bismuth oxyhalide can significantly improve the photocatalytic performance of g-C3N4.

[0005] The doping of Ni ions solves the problem that the photogenerated electrons and holes in g-C3N4 are easy to recombine, greatly improving the photocatalytic performance of the material.

[0006] Based on this, the purpose of the present invention is to solve the problem that the photonic quantum efficiency of g-C3N4 is not high and the effective utilization of visible light is low, and to provide a nickel-doped bismuth oxide halide / g-C3N4 composite catalyst and its preparation method. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst in order to solve the technical problems that the photonic quantum efficiency of g-C3N4 is low and the effective utilization of visible light is low.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is:

[0009] A method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst comprises the following steps: Step 1, g-C3N4 preparation: weighing and mixing melamine and thiourea in a mass ratio of 1:0.2-0.6, or weighing and mixing melamine and hexamethylenetetramine in a mass ratio of 1:0.2-0.6; dissolving in 50-100 ml of deionized water, stirring for 30-90 min, transferring the obtained mixed solution to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction, wherein the hydrothermal reaction temperature is 120-210° C. and the mixture is kept warm for 4-10 h. After that, the suspension is centrifuged and washed with anhydrous ethanol. After washing, it is placed in a drying oven and dried at 80-100°C for 1-5h. The obtained white powder is placed in a crucible with a cover, and the crucible is placed in a muffle furnace. It is heated to 400-600°C at a rate of 2-10°C / min in an air atmosphere, and cooled to room temperature to obtain a light yellow graphene phase g-C3N4 sample; Step 2, preparation of bismuth oxyhalide / g-C3N4: XX-XXmL of solvent, one or more of acetic acid, ethanol, ethylene glycol, and acetonitrile are added to the graphite phase carbon nitride g-C3N4 prepared in step 2, and then KX, X=Cl is added to the g-C3N4 mixed solution. , Br, I, one or more thereof, and Bi(NO3)3•5H2O, the added amount is a g-C3N4 mixed solution, KX, Bi(NO3)3•5H2O mass ratio is 1:1.1:1.7, the mixed solution is ultrasonically dispersed for 10-90 minutes, and then placed in an autoclave for heating at a temperature of 80-210°C for 2-10 hours, the product is centrifuged and washed and dried at a drying temperature of 60-100°C for 0.5-4 hours, and the BiOX-g-C3N4 photocatalyst is obtained by grinding. The BiOX-g-C3N4 photocatalyst is a yellow powder; Step three, Ni doped with halogen oxide Preparation of bismuth / g-C3N4 composite catalyst: Mix one or more of nickel salt, nickel nitrate, nickel sulfate or nickel chloride with the BiOX-g-C3N4 photocatalyst prepared in step 2 according to the designed proportion and add them to a solvent for stirring, wherein the solvent is one or more of acetic acid, ethanol, ethylene glycol, and acetonitrile, and heat the reaction at a set temperature of 80-160°C for 2-8h. After the reaction is completed, naturally cool to room temperature, filter, collect the product, and wash it alternately with deionized water and anhydrous ethanol. Dry the filter residue in an oven at a drying temperature of 60-100°C for 0.5-4h to obtain the product Ni-doped BiOX-g-C3N4 composite catalyst;

[0010] The Ni-doped BiOX-g-C3N4 composite catalyst recovered by the above method is a yellow powder, in which the Ni mass percentage content is 5-20wt%, and the degradation rate is 87.32%-91.78% as determined by the degradation test.

[0011] The present invention provides a technical solution for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, wherein the further preferred technical solution is characterized by:

[0012] 1. In the step 1, melamine and thiourea are weighed and mixed in a mass ratio of 1:0.4-0.5, or melamine and hexamethylenetetramine are weighed and mixed in a mass ratio of 1:0.3-0.5;

[0013] 2. In step 2, the solvent is acetic acid or ethylene glycol, and the amount added is 2-3 times the volume of g-C3N4.

[0014] 3. The ultrasonic dispersion power in step 2 is 50-180w.

[0015] 4. In step 3, the nickel salt is nickel nitrate or nickel sulfate; and the solvent is acetic acid or ethylene glycol.

[0016] Compared with the prior art, the present invention has the following beneficial effects: the present invention uses the photocatalyst BiOX-g-C3N4 as a carrier, and loads the transition metal ion Ni on the BiOX-g-C3N4; due to the special structure and large specific surface area of ​​the carrier BiOX-g-C3N4, it has good adsorption performance, so that the concentration of the solution to be degraded around the composite material is increased, and the concentration of oxygen and organic matter on the surface of BiOX-g-C3N4 is increased; at the same time, Ni ions themselves have certain conductive properties, so Ni-BiOX-g-C3N4 has the advantages of both a conductor and BiOX-g-C3N4, has higher catalytic activity, and the composite material is stable and has better dispersibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0018] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Example 1, a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, comprising the following steps: Step 1, g-C3N4 preparation: melamine and thiourea are weighed and mixed in a mass ratio of melamine to thiourea of ​​1:0.2, dissolved in 50 ml of deionized water, stirred for 30 minutes, and then the resulting mixed solution is transferred to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 120°C and kept warm for 4 hours. After the hydrothermal reaction, the suspension is centrifuged and separated. The mixture was washed with anhydrous ethanol, placed in a drying oven and dried at 80°C for 1h, the obtained white powder was placed in a crucible with a lid, the crucible was placed in a muffle furnace, heated to 400°C at a rate of 2°C / min in an air atmosphere, and cooled to room temperature to obtain a light yellow graphene phase g-C3N4 sample; Step 2, preparation of bismuth oxyhalide / g-C3N4: 1.5 times the volume of g-C3N4 was added to the graphene phase carbon nitride g-C3N4 prepared in step 2, and then 0.54g KCl and 0.86g KCl were added to the 0.5g g-C3N4 mixed solution. Bi(NO3)3•5H2O, ultrasonically disperse the mixed solution, the ultrasonic dispersion power is: 50w; the time is 10min, then place it in an autoclave for heating, the heating temperature is 80℃, the time is 2h, the product is centrifuged and washed, dried, the drying temperature is 60℃, the time is 0.5h, and grind to obtain BiOX-g-C3N4 photocatalyst; Step three, preparation of Ni-doped bismuth oxyhalide / g-C3N4 composite catalyst: according to the designed ratio, 0.1g nickel nitrate is mixed with the BiOX-g-C3N4 photocatalyst prepared in step 2 and added to the solvent for stirring, the solvent is acetic acid, and the reaction is heated at a constant temperature of 80℃ for 2h. After the reaction is completed, it is naturally cooled to room temperature, filtered, the product is collected, and washed alternately with deionized water and anhydrous ethanol. The filter residue is dried in an oven at a drying temperature of 60℃ for 0.5h to obtain the product Ni-doped BiOX-g-C3N4 composite catalyst, which is a yellow powder, wherein Ni 5%, bismuth oxychloride 70%, g-C3N4 25%.

[0020] Example 2, a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, comprising the following steps: Step 1, g-C3N4 preparation: melamine and thiourea are weighed and mixed in a mass ratio of melamine to thiourea of ​​1:0.6, dissolved in 100 ml of deionized water, stirred for 90 minutes, and then the resulting mixed solution is transferred to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 210°C and kept warm for 10 hours. After the hydrothermal reaction, the suspension is centrifuged Separate, wash with anhydrous ethanol, place in a drying oven and dry at 100°C for 5h after washing, put the obtained white powder into a crucible with a lid, put the crucible into a muffle furnace, heat to 500°C at a rate of 5°C / min in an air atmosphere, and cool to room temperature to obtain a light yellow graphene phase g-C3N4 sample; Step 2, preparation of bismuth oxyhalide / g-C3N4: add solvent ethylene glycol to the graphite phase carbon nitride g-C3N4 prepared in step 2 at a volume ratio of 1:2, and then add 0.4g KI and 0.43g to the 0.5g g-C3N4 mixed solution respectively. Bi(NO3)3•5H2O, the mixed solution is ultrasonically dispersed, the ultrasonic dispersion power is: 80w; the time is 80min, and then placed in an autoclave for heating, the heating temperature is 200℃, the time is 5h, the product is centrifuged and washed and dried, the drying temperature is 100℃, the time is 4h, and the BiOX-g-C3N4 photocatalyst is obtained by grinding. The BiOX-g-C3N4 photocatalyst is yellow powder; Step 3, Preparation of Ni-doped bismuth oxyhalide / g-C3N4 composite catalyst : According to the designed ratio, 0.1g of nickel sulfate is mixed with the BiOX-g-C3N4 photocatalyst prepared in step 2 and added to a solvent with stirring. The solvent is acetic acid. The reaction is heated at a set temperature of 100°C for 6 hours. After the reaction is completed, it is naturally cooled to room temperature, filtered, and the product is collected. It is washed alternately with deionized water and anhydrous ethanol. The filter residue is dried in an oven at a drying temperature of 80°C for 4 hours to obtain a Ni-doped BiOX-g-C3N4 composite catalyst. The composite catalyst is a yellow powder, which contains 10% Ni, 60% bismuth oxyiodide, and 30% g-C3N4.

[0021] Example 3, a method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, comprising the following steps: Step 1, g-C3N4 preparation: melamine and hexamethylenetetramine are weighed and mixed in a mass ratio of 1:0.6; dissolved in 80 ml of deionized water, stirred for 60 min, and then the resulting mixed solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction at a temperature of 200°C and kept warm for 8 h. After the hydrothermal reaction, the suspension was centrifuged and dried with an aqueous solution of 100 μg / ml. The mixture was washed with water and ethanol, and then placed in a drying oven and dried at 80°C for 4h. The obtained white powder was placed in a crucible with a lid, and the crucible was placed in a muffle furnace. It was heated to 600°C at a rate of 8°C / min in an air atmosphere, and cooled to room temperature to obtain a light yellow graphene phase g-C3N4 sample. Step 2, preparation of bismuth oxyhalide / g-C3N4: to the graphite phase carbon nitride g-C3N4 prepared in step 2, a solvent ethanol volume of 3 times that of g-C3N4 was added, and then 0.4g KBr and Bi(NO3)3•5H2O were added to the 0.5g-C3N4 mixed solution. 0.43g, the mixed solution is ultrasonically dispersed for 90min, and then placed in an autoclave for heating at a temperature of 210°C for 10h. The product is centrifuged, washed, and dried at a drying temperature of 100°C for 3h. The BiOX-g-C3N4 photocatalyst is ground to obtain a yellow powder. Step 3, preparation of Ni-doped bismuth oxyhalide / g-C3N4 composite catalyst: 0.1g nickel chloride is mixed with the BiOX-g-C3N4 photocatalyst prepared in step 2 according to the designed ratio and added to a solvent for stirring. The solvent is ethyl acetate. The reaction is heated at a set temperature of 100°C for 6h. After the reaction is completed, it is naturally cooled to room temperature, filtered, the product is collected, and washed alternately with deionized water and anhydrous ethanol. The filter residue is dried in an oven at a drying temperature of 100°C for 4h to obtain a product Ni-doped BiOX-g-C3N4 composite catalyst. The composite catalyst is a yellow powder, wherein Ni 20%, bismuth oxybromide 45%, g-C3N4 35%.

[0022] In comparative example 1, the Ni ion doping amount of Example 3 was reduced to 0wt%, and other conditions remained unchanged.

[0023] Degradation experiment:

[0024] Disperse 0.3g of Ni-BiOX-g-C3N4 catalyst into 50 mL of phenol solution with a concentration of 100mg / L. Place the reaction system in a photochemical reactor and stir to adsorb in the dark. Stir in the dark for 30 minutes to reach adsorption-desorption equilibrium. Irradiate with a 300W mercury lamp and start timing. Take a sample every 10 minutes, measure the absorbance of the supernatant at λ=270nm, and calculate the degradation rate. The calculation basis of the degradation rate is as follows:

[0025] According to the Lambert-Beer law, the absorbance was converted into concentration, and the degradation rate of phenol concentration before and after illumination was calculated, which was used to evaluate the photocatalytic activity of Ni-BiOX-g-C3N4. The calculation formula is:

[0026]

[0027] Where: η is the degradation rate of phenol, C0 is the concentration of phenol solution before illumination, and Ct is the concentration of phenol solution after illumination.

[0028] The product result analysis results are shown in Table 1.

[0029] Table 1 Product results analysis

[0030]

[0031] It can be concluded from the data in Table 1 that Examples 1-3 are preparation methods of a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst provided by the present invention, which can load transition metal ions Ni on BiOX-g-C3N4. Due to the special structure and large specific surface area of ​​the carrier BiOX-g-C3N4, it has good adsorption performance, so that the concentration of the solution to be degraded around the composite material is increased, and the concentration of oxygen and organic matter on the surface of BiOX-g-C3N4 is increased. At the same time, Ni ions themselves have certain conductive properties, so Ni-BiOX-g-C3N4 has the advantages of both conductors and BiOX-g-C3N4, has higher catalytic activity, and the composite material is stable and has better dispersibility.

[0032] The above are only preferred embodiments of the present invention. It should be noted that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field of chemistry, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst, characterized in that: The following steps are involved: Step 1, preparation of g-C3N4: weigh melamine and thiourea in a mass ratio of 1:0.2-0.6 and mix them, or weigh melamine and hexamethylenetetramine in a mass ratio of 1:0.2-0.6 and mix them; dissolve in 50-100 ml of deionized water, stir for 30-90 min, and transfer the resulting mixed solution to a polytetrafluoroethylene-lined stainless steel autoclave for hydrothermal reaction. The hydrothermal reaction temperature is 120-210°C and kept warm for 4-10h. After the hydrothermal reaction, the suspension is centrifuged and washed with anhydrous ethanol. After washing, it is placed in a drying oven and dried at 80-100°C for 1-5h. After drying, the obtained white powder is placed in a crucible with a cover, and the crucible is placed in a muffle furnace. It is heated to 400-600°C at a rate of 2-10°C / min in an air atmosphere, and cooled to room temperature to obtain a light yellow graphene phase g-C3N4 sample; Step 2, preparation of bismuth oxyhalide / g-C3N4: add a solvent, one or more of acetic acid, ethanol, ethylene glycol, and acetonitrile, to the graphene phase carbon nitride g-C3N4 prepared in step 2, the volume of the solvent added is 1.5-3 times that of g-C3N4, stir and mix, then add KX, X=one or more of Cl, Br, I, and Bi(NO3)3•5H2O to the g-C3N4 mixed solution, the added amount is g-C3N4, KX, Bi(NO3)3•5H2O mass ratio is 1:1.1:1.7, the mixed solution is ultrasonically dispersed for 10-90min, then placed in an autoclave for heating at a temperature of 80-210°C for 2-10h, the product is centrifuged, washed and dried at a drying temperature of 60-100°C for 0.5-4h, and ground to obtain BiOX-g-C3N4 photocatalyst; Step 3, preparation of Ni-doped bismuth oxyhalide / g-C3N4 composite catalyst: according to the designed proportion, nickel salt, one or more of nickel nitrate, nickel sulfate or nickel chloride, is mixed with the BiOX-g-C3N4 photocatalyst prepared in step 2 and added to a solvent for stirring, wherein the solvent is one or more of acetic acid, ethanol, ethylene glycol, and acetonitrile, and the reaction is carried out at a set temperature of 80-160°C for constant temperature heating for 2-8h. After the reaction is completed, it is naturally cooled to room temperature, filtered, the product is collected, and washed alternately with deionized water and anhydrous ethanol. The filter residue is dried in an oven at a drying temperature of 60-100°C for 0.5-4h to obtain a product Ni-doped BiOX-g-C3N4 composite catalyst; The Ni-doped BiOX-g-C3N4 composite catalyst is a yellow powder, wherein the Ni content is 5-20wt% by weight, and the degradation rate is 87.32%-91.78% as determined by a degradation test.

2. The method for preparing the nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst according to claim 1, characterized in that: In step 1, the melamine and thiourea are weighed and mixed in a mass ratio of 1:0.4-0.5, or the melamine and hexamethylenetetramine are weighed and mixed in a mass ratio of 1:0.3-0.

5.

3. The method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst according to claim 1, characterized in that: The solvent in step 2 is acetic acid or ethylene glycol, and the added volume is 2-3 times that of g-C3N4.

4. The method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst according to claim 1, characterized in that: In step 2, the ultrasonic dispersion power is 50-180w.

5. The method for preparing a nickel-doped bismuth oxyhalide / g-C3N4 composite catalyst according to claim 1, characterized in that: In step 3, the nickel salt is nickel nitrate or nickel sulfate; and the solvent is acetic acid or ethylene glycol.

Citation Information

Patent Citations

  • Methods of synthesizing an oxidant and applications thereof

    AU2001280529A1

  • Preparation method and application of g-C3N4 grafted bismuth oxyhalide microsphere photocatalyst

    CN108607590A